PERSEPSI SISWA TERHADAP PENGGUNAAN MODUL PRAKTIKUM BIO BATERAI DALAM PEMBELAJARAN FISIKA SMA MATERI ENERGI TERBARUKAN - Pawarangan, Ishak; Tumewu, Widya Anjelia; Mawuntu, Vicky Julius; Kumendong, Igreya Mitchell (Charm Sains: Jurnal Pendidikan Fisika, 2024)
This study aims to examine students' perceptions of the use of a bio-battery practicum module utilizing coffee grounds in physics education on the topic of renewable energy. The research involved 12 students from SMA Negeri 2 Tomohon as participants. The evaluation instrument consisted of a questionnaire with 11 questions grouped into three primary indicators: module appearance, material presentation, and module benefits. The findings revealed that the module appearance indicator was rated as excellent on three questions (100%, 83.33%, and 100%) and good on one question (66.67%). The material presentation indicator received excellent ratings across all questions, ranging from 83.33% to 100%. Similarly, the module benefits indicator achieved excellent ratings for all questions (100%). Despite these positive results, a few neutral responses were observed on questions concerning the module’s design and illustrations (33.33% and 16.67%) and material clarity (16.67%). Overall, the module demonstrated a high level of effectiveness, with the majority of scores exceeding 76%, placing it in the "excellent" category. These results underscore the significant potential of the bio-battery practicum module as an innovative educational tool to enhance students' understanding of renewable energy concepts at the high school level.